ANALISIS HUKUM PARTISIPASI PEREMPUAN UNTUK MENDUKUNG KEBERLANJUTAN UMKM DI KABUPATEN ACEH TENGAH - Maria Sanola; Mudfar Alianur (Jurnal Sains Riset, 2025)
This study examines the legal framework that supports women’s participation in Micro, Small, and Medium Enterprises (MSMEs) in Central Aceh Regency and formulates policy recommendations to promote gender-responsive economic empowerment. Although women constitute a significant portion of MSME actors and contribute substantially to local economic development, they continue to face major barriers, including limited access to capital, inadequate training and business assistance, and the absence of regulations that specifically address their needs. Using an empirical legal research approach with qualitative methods, data were collected through in-depth interviews, observations, and analysis of secondary documents from the Cooperative and MSME Office. The findings reveal structural inequalities in access to financial resources, minimal managerial and digital marketing training, weak implementation of existing MSME regulations, and persistent gender-based cultural constraints rooted in patriarchal norms. These challenges hinder women’s ability to develop their businesses and participate actively in the regional economy. The study recommends strengthening gender-responsive local regulations, expanding inclusive financial schemes, providing sustainable entrepreneurship training, and promoting cultural transformation to support women’s roles in public and economic spheres. This research is expected to serve as a reference for policymakers in creating an inclusive and sustainable MSME ecosystem that empowers women in Central Aceh Regency.